66 KETOSIS-PRONE TYPE 2 DIABETES MELLITUS. (1st January 2006) - Smiley, D.; Umpierrez, G.
Abstract : Many newly diagnosed African Americans with diabetic ketoacidosis (DKA) display clinical, metabolic, and immunological features of type 2 diabetes during follow-up. Their initial presentation is acute and without precipitating cause. Most patients are able to discontinue insulin therapy within a few weeks/months of follow-up. This clinical presentation is common, affecting 20-50% of newly diagnosed black and Hispanic patients with DKA. This subtype of diabetes is referred to as diabetes type 1B, idiopathic type 1 diabetes, atypical diabetes, Flatbush diabetes, type 1.5 diabetes, and, more recently, ketosis-prone type 2 diabetes (KPDM). We reviewed current knowledge regarding the clinical presentation, metabolic, and immunologic features of subjects with this "atypical " form of diabetes. We performed a computerized search of biomedical journal literature from Medline, PubMed, and Ovid from 1/1966 to 10/2005. English-language original articles found under the subject headings "ketosis-prone type 2 diabetes " and "atypical diabetes " were reviewed. In this analysis we included 484 cases (429 blacks, 39 Hispanics, 8 Asians, 8 Caucasians) from 7 series reported from America, Europe, Africa, and Asia. Clinical characteristic include a mean age of 40 6 3 years, male gender 67% 6 9, new-onset diabetes: 83%, % family history: 80 6 5, % positive antibodies: 7.1 6 7, % patients who attained remission: 59 6 15, A1C at presentation: 13.2 6 0.6%, and A1C at remission: 7.0 6 1.2%. At presentation, they have markedly impaired insulin secretion and insulin action, but intensified treatment improves b-cell function and insulin sensitivity during follow-up. Determination of autoimmune markers (islet cell and glutamic acid decarboxylase antibodies) and measurement of insulin secretion (basal or glucagon-stimulated C-peptide levels) may be useful in predicting near-normoglycemic remission. Our analysis indicates that what was once considered as "atypical diabetes " is a common clinical presentation among newly diagnosed black and Hispanic patients with DKA. This subtype of diabetes with phasic insulin dependence represents a subset of type 2 diabetes and confirms the wide spectrum of clinical presentation of type 2 diabetes.